Bufo versus Lacrónica. Current Drifts of Knowledge Production in Latin America - Cimadevilla, Gustavo (2018)
The amount of postgraduate dissertations in Communication that occur annually in Latin America would indicate that the area has a permanent power of results to disseminate. However, the impressions we have about the production of dissertations and master and doctoral theses do not confirm it. If at some point it was considered relevant to develop reasoning that would provoke existing knowledge, and invite them to think new realities and discuss old postulates about legitimized theories, today new writings are adapted to meet the guidelines of research projects oriented by sequential objectives in which proposals in particular do not excel, and therefore do not off er striking results. Should this worry us if the social sciences claim to have visibility and social value? The present text analyzes why in these models of academic production there are few novelties and only off ers some alternatives to rethink the relevance, a key aspect and of interest for researchers that promote the generation of knowledge for the social fabric around ALAIC.